Webdocumentaire et histoire de la télévision suisse - Roxane Gray; Gabrielle Duboux (Conserveries Mémorielles)
For the commemoration of the 50th anniversary of Swiss Radio Television (RTS)’s magazine Temps Présent (RTS, 1969-today), we participated in the production of a web documentary on the history of the programme. This project is the result of an interdisciplinary joint effort carried out by RTS, the Faculty of Arts of the University of Lausanne, and the Academy of Journalism and Media of Neuchâtel (AJM). Three years after the broadcast of this web documentary in April 2019, we look back on this experience of research and historical mediation, and present the different stages of this French Swiss collaboration. This review is part of a wider reflection on epistemological and historiographical issues. The focus is on the narrative modes and broadcasting of Switzerland’s televisual history. We analyze the contributions of this experience as well as the methodological problems encountered, be that in the constraints linked to the mediatisation of oral testimonies or the adaptation of the historical narrative to a delinearised visualization. These reflections are applied to a practical case around the scientific approach of valorizing the place of women in the history of Temps Présent.